Analysis of the Relationship between Organizational Commitment and Teacher Professionalism on Improving the Quality of Education in Vocational High Schools - Aprilia, Priska; Ade Saputri, Noviyanti; Aslamiah, Aslamiah; Cinantya, Celia (Riwayat: Educational Journal of History and Humanities, 2024)
This study investigates the relationship between organizational commitment and teacher professionalism in improving the quality of education in vocational high schools. Organizational commitment is defined as the emotional and psychological attachment teachers have to their institutions, and its positive impact on teacher engagement and student outcomes has been well-documented. Teacher professionalism, which includes continuous development, ethical practices, and alignment with industry needs, is particularly crucial in vocational settings. The synergy between these two factors leads to a culture of excellence where teachers are highly motivated and dedicated to delivering quality education. This research adopts a qualitative approach, utilizing interviews, focus group discussions, and thematic analysis to explore these dynamics in vocational high schools. The findings highlight the importance of professional development opportunities and supportive work environments in fostering teacher commitment and professionalism. Furthermore, school leadership plays a vital role in cultivating this synergy by providing recognition, creating collaborative environments, and offering incentives for professional growth. The study concludes by recommending policy interventions that focus on enhancing both organizational commitment and professionalism to ensure sustainable improvements in vocational education quality.